Disambiguation of Tafsir Khazin in Muqodimah and its application in Tafsir Lubab al-Ta’wil fi Ma’ani al-Tanzil - Zakiyah, Ermita (Jurnal Studi Al-Qur’an, 2024)
The purpose of this study is to make the disambiguation structure of tafsir khazin in Muqoddimah and its application in Tafsir Lubab al-Ta’wil fi Ma’ani al-Tanzil, tafsir al-Khazin is not free from criticism because of the israiliyat history that has no source. In contrast, tafsir khazin is tafsir khazin, including classical tafsir, which summarizes the book of tafsir Ma’alim al-Tanzil by Abu Muhammad Husayn ibn Mas’ud al-Baghawi (d.510 AH), which includes bil-Ma’tsur but tafsir khazin after Being studied he uses bi al-ra’y in his interpretation. The change is then examined in the disambiguation structure with library analysis. H) which includes bil-ma’tsur but tafsir khazin. After being studied, he uses bi al-ra’y in his interpretation. The change is then examined in the disambiguation structure with library research and descriptive-analytical analysis to explore and analyze the structure of disambiguation in muqoddimah and its application in his tafsir. This article concludes that there is disambiguation between muqoddimah tafsir khazin and his tafsir.